Geochemistry of arc alkaline magmatism of Java Island, Sunda Arc: a statistical review - Handini, Esti (2022)
Alkaline magmatism develops in the rear arc area of Java, Sunda Arc, at different range of slab depth; ∼270-580 km in central section and ∼150 km in the east. We collate published geochemical data of volcanic rocks from four alkaline volcanoes (Muria, Lasem, Bawean, and Ringgit-Beser) and perform statistical analysis to evaluate geochemical characteristics of each suite. A set of major and trace elements is scaled and transformed using principal component analysis (PCA) and then followed by implementation of k-means algorithm to cluster the data points based on Euclidian distances. K-means clustering of the dataset suggests that Central Java alkalines are most elevated in K2O and total alkali. The algorithm further suggests that Muria samples can be clustered into two, owing to these components. These two clusters, however, are not well reflected on trace element-based clustering. Lasem volcanics show distinct cluster high in Na2O/K2O and SiO2, while Bawean samples are mixed into both Muria clusters. Ringgit-Beser alkalines show two distinct clusters tied to MgO and enrichment in Ba, Rb, and Sr. Our findings suggest that the potassium and LILE enrichment in these alkaline rocks is independent of slab depth and is most likely regulated by tectonic-related arc segmentation in Java subduction zone.